The problem of classification of international tourism functions - Chaika, Tetiana (My University, 2023)
Nowadays, there is a certain inconsistency in approaches to the classification of the functions of international tourism. The analysis of the main approaches to the typology of international tourism functions has led us to conclude that it is appropriate to consider the classification system of international tourism functions as a hierarchical structure. Supporting the previously expressed positions of scientists, we believe that at the first (least detailed) level of the classification system it is appropriate to single out three main blocks of functions of international tourism: social; economic; humanitarian. At the next hierarchical level, it is possible to detail the content of the above-mentioned blocks of international tourism functions. A comparison between the functions of tourism and those of international tourism leads to the conclusion that international tourism is a phenomenon in its own right with a significant impact on the evolution of the global human community in the context of sustainable development.

Наразі спостерігається певна неузгодженість підходів до класифікації функцій міжнародного туризму. Аналіз основних підходів до типологізації функцій міжнародного туризму дозволив зробити висновок про доцільність розгляду системи класифікації функцій міжнародного туризму як ієрархічної структури. Підтримуючи позиції вчених, які раніше вже висловлювалися, вважаємо, що на першому (найменш деталізованому) рівні системи класифікації доцільно виділити три основні блоки функцій міжнародного туризму: соціальний; економічний; гуманітарний. На наступному ієрархічному рівні маємо можливість деталізувати зміст вищезгаданих блоків функцій міжнародного туризму. Порівняння функцій туризму та функцій міжнародного туризму дозволяє зробити висновок про те, що міжнародний туризм є самостійним феноменом, який істотно впливає на еволюцію світової людської спільноти в контексті сталого розвитку.
Проблема типологізації функцій міжнародного туризму
Keywords: international tourism; functions of international tourism; hierarchical structure; sustainable development; міжнародний туризм; функції міжнародного туризму; ієрархічна структура; сталий розвиток